THE ROLE OF INSTAGRAM MEDIA IN BRANDING DESTINATIONS AMONG YOUTH IN BUKITTINGGI CITY - Jovan Abdul Asyraf; Enok Maryani; Rini Andari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of this study was to identify the role of Instagram media in Destination Branding among teenagers in Bukittinggi City. The method used in this study is a qualitative descriptive method, to present a complete picture of the role of Instagram media with the Instagramable phenomenon in the formation of branding destinations among final year teenagers. The results of this study are to identify the extent to which Instagram media plays a role in the formation of branding destinations among late-level teenagers. This research was conducted by discussing Tourism, Branding Destinations, New Media (Instagram), Instagramable, and Gen Z specifications for late teens with an age range of 18-21 years and taking a case study in Bukittinggi City.